Original sin [large type] : President Biden's decline, its cover-up, and his disastrous choice to run again - Tapper, Jake; Thompson, Alex (Random House Large Print, 2025)
"[A]n unflinching and explosive reckoning with one of the most fateful decisions in American political history: Joe Biden's run for reelection despite evidence of his serious decline -- amid desperate efforts to hide the extent of that deterioration. In Greek tragedy, the protagonist's effort to avoid his fate is what seals his fate. In 2024, American politics became a Greek tragedy. Joe Biden launched his successful 2020 bid for the White House with the stated goal of saving the nation from a second Trump presidential term. He, his family, and his senior aides were so convinced that only he could beat Trump again, they lied to themselves, allies, and the public about his condition and limitations. At his debate with Trump on June 27, 2024, the consequences of that deception were exposed to the world. It was shocking and upsetting. Now the full, unsettling truth is being told for the first time. Jake Tapper and Alex Thompson take us behind closed doors and into private conversations between the heaviest of hitters, revealing how big the problem was and how many people knew about it. From White House staffers at the highest to lowest levels, to leaders of Congress and the Cabinet, from governors to donors and Hollywood players, the truth is finally being told. What you will learn makes President Biden's decision to run for reelection seem shockingly narcissistic, self-delusional, and reckless--a desperate bet that went bust -- and part of a larger act of extended public deception that has few precedents. The story the authors tell raises fundamental issues of accountability and responsibility that will continue for decades. The irony is biting: In the name of defeating what they called an existential threat to democracy, Biden and his inner circle ensured it, tossing aside his implicit promise to serve for only one term, denying the existence of health issues the nation had been watching for years, dooming the Democrats to defeat. The decision to run again, the Original Sin of this president, led to a campaign of denial and gaslighting, leading directly to Donald Trump's return to power and all that has happened as a consequence. Rarely does hubris meet nemesis more explosively. Wherever you stand on the political spectrum, Original Sin is essential reading." --